Continuous buccolingual masticatory dyskinesia in Parkinson's disease. (25th September 2012) - Meyniel, Claire; Derkinderen, Pascal; Giumelli, Bernard; Damier, Philippe
Abstract : Usually, levodopa-induced dyskinesia does not remain unchanged throughout the day in Parkinson's disease (PD) patients and varies according to the level of correction of PD symptomatology provided by the treatment. We observed two PD patients with unusual buccolingual masticatory movements which did not seem to fluctuate, either throughout the day during dopaminergic treatment or during a standardised levodopa challenge. After their dopaminergic treatment had been changed to a less pulsatile form of administration (ie, the use of dopamine agonist alone in the first patient and an increase in the dosage of dopamine agonist with a low dose of levodopa in the second), these abnormal movements totally disappeared in the first patient and were greatly improved in the second. These observations suggest that levodopa can have prolonged effects (several days) and induce prolonged buccolingual masticatory movements similar in type to those classically observed with dopamine receptor antagonists (neuroleptics).